Establishing Critical Elements of Energy Management for Sustainable Campus Development - Ali Ashgar, Siti Kartini (International Journal of Sustainable Energy Planning and Management, 2025)
A comprehensive energy management guideline tailored to higher education institutions in Malaysia is essential for advancing sustainable campus development. As energy consumption rises due to infrastructure growth and increasing student populations, existing sustainable campus tools often fall short in fully integrating key energy management elements. This research focuses on identifying critical energy elements that contribute to campus sustainability. A review of 23 international sustainability frameworks, including STARS, Green Mark, GBI, and UI GreenMetric, revealed that most tools lack a holistic approach to energy management. A framework with 11 essential energy elements is proposed, covering both technical (retrofitting, building envelope, efficient equipment, mechanical systems, and renewable energy) and management aspects (organizational structure, energy policy, planning, energy auditing, reporting, and awareness). UI GreenMetric was selected as the baseline reference due to its alignment with the Malaysian university context. A structured questionnaire was applied in a case study at Universiti Malaysia Sabah to evaluate the relevance of each element. Judgmental sampling targeted. Data were analyzed using descriptive statistical methods including frequencies and mean scores. The findings establish a set energy management elements and highlight the importance of combining critical technical and management aspects to support sustainable energy practices across Malaysian higher education campuses.